2006
DOI: 10.1029/2005jd006096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land use on Costa Rican tropical montane cloud forests: Sensitivity of orographic cloud formation to deforestation in the plains

Abstract: [1] The current study provides new insights into the coupling of land use in lowland and premontane regions (i.e., regions below 1000 m) and orographic cloud formation over the Monteverde cloud forests. Rawinsondes launched during the Land Use Cloud Interaction Experiment (LUCIE) together with those from the National Centers for Environmental Prediction (NCEP) provided profiles that were used to drive the Colorado State University Regional Atmospheric Modeling System (CSU RAMS) model, which simulated three rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 36 publications
10
127
1
6
Order By: Relevance
“…These results are in agreement with the increases in cloud base heights observed over the Monteverde region of Costa Rica due to localized deforestation [Lawton et al, 2001;Nair et al, 2003;Ray et al, 2006], although these previous studies did not include the effects of global climate change in the configuration of their modeling experiments and conclusions.…”
Section: Comarazamy and González: Regional And Local Climate Changes supporting
confidence: 81%
See 2 more Smart Citations
“…These results are in agreement with the increases in cloud base heights observed over the Monteverde region of Costa Rica due to localized deforestation [Lawton et al, 2001;Nair et al, 2003;Ray et al, 2006], although these previous studies did not include the effects of global climate change in the configuration of their modeling experiments and conclusions.…”
Section: Comarazamy and González: Regional And Local Climate Changes supporting
confidence: 81%
“…The liquid water mixing ratio (g kg −1 ) contains the amount, in total mass, of cloud droplets and raindrops per kilogram of dry air, and therefore accounts for the two completely nonfrozen cloud microphysics hydrometeors in the atmospheric regional model cloud module that indicate the cloud formation and rain development process in the tropics. It has been reported that changes in wind patterns and vertical wind motions should also produce changes in cloud base heights, an important parameter in tropical montane cloud forests [Hamilton et al, 1993;Bruijnzeel and Proctor, 1993;Still et al, 1999;Nair et al, 2003;Ray et al, 2006;Lawton et al, 2011]. A montane cloud forest is defined as a tropical or subtropical moist forest in elevated terrain in which the cloud base is persistently or seasonally at or below the vegetation canopy level.…”
Section: Comarazamy and González: Regional And Local Climate Changes mentioning
confidence: 99%
See 1 more Smart Citation
“…Cloud water provides an important source of moisture in tropical montane cloud forests during the dry season (18,19), when salamanders would be expected to be under the highest physiological stress; most cloud forest habitats contain little or no standing water, and plethodontid salamanders depend on adequate moisture for surface activity because of their permeable skins (20). Lawton et al (21) and Nair et al (22) showed that deforestation in lowland and premontane regions leads to an elevational increase of the cloud base, and Ray et al (23) used a modeling approach to demonstrate that deforestation in the lowlands of Costa Rica has led to an increase in mist-free conditions in the cloud forest at Monteverde. The Pacific lowlands and premontane areas of Guatemala have been extensively deforested; although the Pacific plain deforestation occurred before the salamander sampling in the 1970s, much of the premontane forest disappeared during and after this time (24).…”
Section: Discussionmentioning
confidence: 99%
“…In Costa Rica, for example, complete deforestation of lowland and premontane regions (\1000-1400 m.a.s.l.) was hypothesized to generate an upward 50-100 m shift in cloudbank elevation (Ray et al 2006). Such an effect would impart considerable influence on any project designed to increase cloudwater interception at lower elevations.…”
Section: Implementing Programs For Water Servicesmentioning
confidence: 99%